Św. Piotr biskupem Rzymu? - Pałucki, Jerzy (Vox Patrum, 2008)
The primacy of the Bishop of Rome is an essential, if not a fundamental element of the unity of Church and belongs to the mainstream of ecclesiology throughout its whole history. It is anchored in the study of the doctrine of the New Testament and from the very beginning, starting from the oldest patristic sources, such as the Epistle of Saint Clement of Rome to Corinthians and Ignatius of Antioch’s Epistles, there have been utterances indicating Saint Peters extraordinary role in the universal Church and the significance of his stay in Rome and the foundation of the local Christian community there. The Church Fathers also emphasize that Peter is present in all fundamental events related to the foundation of the Church and it was him who was entrusted with the care for its unity by Jesus. The first writers who start to describe Peter as the Bishop of Rome are Tertullian and Cyprian, who teaches that the Bishop’s authority is like the Apostles’ authority and uses the term cathedra Petri referring to Rome. Although Saint Irenaeus attributes the foundation of the Roman Church to Peter and Paul, in the course of years, especially after the transfer of the Capital of the Empire to Constantinople, he also puts the name of Peter at the top of the list of Roman Bishops. Many biblical scholars and patrologists also emphasize that Paul never laid claim to be the Bishop of Rome.